Consideration of total available N supply reduces N fertilizer requirement and potential for nitrate leaching loss in tomato production - Soto Bravo, Freddy (2015)
Effects of increasing total available N (TAN) on agronomic performance, apparent recovery of TAN (ARTAN), NO3 leaching and soil mineral N accumulation were examined in two tomato crops. Total available N was considered to be the sum of soil mineral N at planting, N mineralized from organic material (soil organic matter and manure), and mineral N fertilizer applied by fertigation. In each crop, four different mineral N fertilizer rates were applied as different N concentrations (N1: 0.6–1.1 mM, N2: 4.4–5.2 mM, N3: 13.4–13.6 mM, N4 20.5–21.7 mM) in nutrient solutions applied in all irrigations every 1– 4 days throughout the crop. N3 treatments corresponded to local commercial practice. The first crop was grown in autumn–winter 2010 (AW-2010) and the second in spring 2011 (S-2011). For the two crops, TAN values were 165–215 kg N ha 1 in N1, 287–361 kg N ha 1 in N2, 563–667 kg N ha 1 in N3 and 847– 976 kg N ha 1 in N4. In both crops, maximum fruit production was obtained with the N2 treatments. ARTAN decreased exponentially as TAN increased, from values of close to 1.0 for N1 treatments to approximately 0.3 for N4 treatments. The linear relationship between NO3 leaching and TAN had a shallow slope, with a maximum leaching loss of 36–40 kg N ha 1 in the N4 treatments; NO3 leaching loss was limited by small drainage volumes associated with good irrigation management. There was an exponential increase in residual soil mineral N with increasing TAN. For N3 treatments, corresponding to common local management practices, residual soil mineral N was 234–262 kg N ha 1, and for N4 treatments was 484–490 kg N ha 1. Therefore, increasing TAN very strongly increased the potential for subsequent N loss. Where TAN was excessive to crop N requirements, limiting NO3 leaching loss (measured using lysimeters) by good irrigation practices was considered to only delay NO3 leaching loss. The N3 treatments of 13–14 mM of N that corresponded to local practice were associated with a large potential N loss. Based on TAN, the optimal treatment was N2 of 4–5 mM which was associated with maximum fruit production and a relatively very small potential loss of N. The results demonstrated that by considering (i) TAN rather than just fertilizer N, and (ii) mineral N fertilizer as a supplement to other N sources, that maximum production can be achieved with high ARTAN and with a much reduced risk of N loss to the environment.